FAMILY CHARACTERISTICS, EATING PARENTING AND TYPES OF DISEASES WITH TODDLER NUTRITIONAL STATUS (HEALTH STUDY AT DEWANTARA HEALTH CENTER OF NORTH ACEH REGENCY) - Noviana Zara (Indonesian Journal of Medical Anthropology, 2022)
This study discusses the relationship of family characteristics, parenting and types of diseases with the nutritional status of toddlers in the Dewantara Health Center of North Aceh Regency. The purpose of this study was to find out the relationship of maternal characteristics, parenting and types of diseases with the nutritional status of toddler patients in the Dewantara Health Center of North Aceh Regency in 2017. This study uses a quantitative approach with this type of observational research with a cross sectional design with the entire population of toddlers who came during the study at Dewantara Health Center. Sampling technique using clusters where data collection uses kuesionoer and analyzed using chi squaretest. The results showed that among the variables related to nutritional status were obtained variables of family characteristics (maternal knowledge, toddler work, family income), parenting and types of diseases. The results of the multivariate test for the most dominant variable related to the nutritional status of toddlers in the multivariate analysis were family income variables (p=0.002 Exp (β)=6,380 95%CI 2,009-20,257) where family income <Rp.2,500,000 was 6 times more likely to experience less nutritional status than family income >Rp.2,500,000.